2011
DOI: 10.1097/igc.0b013e3182131f36
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of CD4+and CD8+T Cell Infiltration Within Cancer Cell Nests in Vulvar Squamous Cell Carcinoma

Abstract: These data support the statement that CD4⁻ and CD8+ T cells cooperate within cancer cell nests, but this spontaneous immune reaction is an individual feature not influencing the prognosis. Intratumoral CD4+ T cells might control or reflect the immune responses against cancer cells, whereas CD8+ T cells do not seem to work as sufficient effectors in tumor tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 19 publications
5
42
0
Order By: Relevance
“…In this cohort of 286 vulvar carcinoma patients, intra-tumoral CD8 + and Foxp3 + T-lymphocytes were present in 96.3% and 95.1% of the cases. In agreement with results of a recently published study in vulvar carcinoma [23], we did not find an association between the number of T-lymphocytes and survival of vulvar carcinoma patients. This result is in contrast with studies previously performed in endometrial [9,11], ovarian [10,30] and cervical carcinoma [31].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this cohort of 286 vulvar carcinoma patients, intra-tumoral CD8 + and Foxp3 + T-lymphocytes were present in 96.3% and 95.1% of the cases. In agreement with results of a recently published study in vulvar carcinoma [23], we did not find an association between the number of T-lymphocytes and survival of vulvar carcinoma patients. This result is in contrast with studies previously performed in endometrial [9,11], ovarian [10,30] and cervical carcinoma [31].…”
Section: Discussionsupporting
confidence: 83%
“…In vulvar carcinoma, evidence for the (prognostic) role of the immune system in vulvar carcinoma is scarce [23,24] and research is warranted on this subject. Therefore, this study aimed to determine the prognostic role of several aspects of the immune system in vulvar carcinoma patients.…”
mentioning
confidence: 99%
“…Lack of prognostic significance of adaptive immune effectors and regulatory T cells described by others [31] was previously confirmed by our group for nearly the same cohort [19, 20]. All these findings have suggested no place for immunotherapy for vulvar cancer patients.…”
Section: Discussionsupporting
confidence: 78%
“…Data on TILs in remaining 76 vSCCs were retrieved from our previous studies [19, 20, 21]. Data on p16 INK4a and (hr) HPV status were retrieved from our recent study [8].…”
Section: Methodsmentioning
confidence: 99%
“…13–17 Gene expression profiling has shown that T-cell activity is decreased in SCC, as shown by downregulation of activation maker CD69 and impaired secretion of granzyme B and inducible nitric oxide synthase (iNOS). 10 In addition, myeloid-derived suppressor cells are present in SCC and function to impair T cell–mediated immunity by secreting nitric oxide in the tumor microenvironment.…”
Section: The Tumor Microenvironment Of Squamous Cell Carcinomamentioning
confidence: 99%